Bank’s Financial Performance based on Solvency Ratio Before and During the Covid- 19 Pandemic. - Nurul Fauziyyah; Novita Ayu Nur Maulidah (International Journal of Entrepreneurship and Tourism, 2023)
This study aims to compare the financial performance of conventional banks listed on the IDX before and during the covid-19 pandemic (2019 to 2020) through solvency ratios. The population used in this study is companies listed in the finance sector on the Indonesia Stock Exchange among 2019 to 2020 as many as 106 companies. By using purposive sampling, 42 conventional banking companies were obtained, so that the sample of this study amounted to 84 because the research data used is 2019 to 2020. The Wilcoxon's Signed Ranks Test is used as a hypothesis analysis in this study by testing capital ratio, primary ratio, and risk assets ratio as solvency analysis. The results found from this study through the Wilcoxon test show that there is no difference in the financial performance of conventional banks before and during the covid-19 pandemic as measured by the solvency ratio.